MODERN METHODS AND TECHNOLOGIES IN BIOLOGY EDUCATION: THEIR IMPACT ON STUDENTS’ PERSONAL DEVELOPMENT - Anarbekkyzy B.; Anarbekova G.D. (Interdisciplinary Science Studies, 2025)
This bibliographic analysis provides a comprehensive examination of the impact of modern methods and technologies used in biology education on students’ personal development. The study includes an analysis of international literature and identifies the relationship between personal development and contemporary instructional methods. The findings emphasize that the influence of biology as a school subject on students’ personal development is directly connected to how and in what ways teachers deliver instruction. According to the analysis, the use of critical thinking strategies, digital-innovative methods, as well as project-based and research-oriented activities, positively contributes to students’ emotional, social, and intellectual development. Therefore, the effective integration of modern teaching methods in biology education serves as an important tool that enhances students’ life competencies and supports their personal development